Optimal Placement and Sizing of Active Power Line Conditioners for Minimizing Power Quality Problems - Swathisriranjani M; Mohananthini K; Ranjitha M; Baskar S; Kavitha D (Institute of Advanced Engineering and Science, 2017)
In this paper, a problem of allocation and sizing of multiple active power-line conditioners (aplcs) in power systems is handled with novel formulation. The utilized objective function comprises two main factors such as reduction of total harmonic distortion and the total cost of active power-line conditioners (aplcs). The formulated problem is solved by optimization technique SHUFFLE FROG LEAP ALGORITHM(SHFLA) using MATLAB. To evaluate the competence of the proposed formulation, the IEEE 18-bus distorted distribution test system is employed and investigated with various number of aplcs placement. These cases are based on the discrete and limited size for aplcs, requiring the optimization method to solve the constrained and discrete nonlinear problems. The comparison of results in this paper showed that the proposed SHFLA is the most effective result among others in determining optimum location and size of APLC in distribution systems.